2014
DOI: 10.1007/978-3-319-01781-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Multi-class SVM Based Classification Approach for Tomato Ripeness

Abstract: Abstract. This article presents a content-based image classification system to monitor the ripeness process of tomato via investigating and classifying the different maturity/ripeness stages. The proposed approach consists of three phases; namely pre-processing, feature extraction, and classification phases. Since tomato surface color is the most important characteristic to observe ripeness, this system uses colored histogram for classifying ripeness stage. It implements Principal Components Analysis (PCA) alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…SVM tries to find an optimal separating hyperplane which effectively separates between classes for solving the classification problem [19]. SVM aims to maximize the margin around a hyperplane that separates a positive class from a negative class [3,20,21,22]. Consider a training dataset with n samples (x 1 ,y 1 ), (x 2 , y 2 ), ...., (x n ,y n ).…”
Section: Support Vector Machinementioning
confidence: 99%
See 2 more Smart Citations
“…SVM tries to find an optimal separating hyperplane which effectively separates between classes for solving the classification problem [19]. SVM aims to maximize the margin around a hyperplane that separates a positive class from a negative class [3,20,21,22]. Consider a training dataset with n samples (x 1 ,y 1 ), (x 2 , y 2 ), ...., (x n ,y n ).…”
Section: Support Vector Machinementioning
confidence: 99%
“…The Support Vector Machine (SVM) classifier is a theoretically superior machine learning methodology that used for classification and regression of highdimensional datasets with great results [3,19,20,21,22]. SVM tries to find an optimal separating hyperplane which effectively separates between classes for solving the classification problem [19].…”
Section: Support Vector Machinementioning
confidence: 99%
See 1 more Smart Citation
“…Correlation was obtained between histogram of each color system and maturity. In the study, highest value were showed at G(36) and R (35) in RGB color space and at L(50) in L*a*b* color space. The experiments also revealed that with increase of maturity the level of a* increases and b* remains unchanged.…”
Section: Classification Of Recognized Tomatoesmentioning
confidence: 78%
“…Authors Elhariri et al [35], investigated the multiclass support vector machine (SVM) approach and random forest (RF) for the estimation of tomato and bell pepper ripeness. A dataset of total 250 images for tomato and 175 images of bell-pepper has been collected from farm.…”
Section: Classification Of Recognized Tomatoesmentioning
confidence: 99%